Formation of epitaxial InSb films on semi-insulating GaAs(100) by explosive thermal evaporation: their structure and electrical properties - Kolesnikova, Evgenia A.; Uglov, Vladimir V.; Kuleshov, Andrey K.; Rusalsky, Dmitry P. (Journal of the Belarusian State University. Physics, 2021)
In the present work, the influence of the deposition temperature of InSb films on semi-insulating GaAs(100) on their phase composition, crystal perfection and electrical properties was investigated. The InSb films of various extent of crystal perfection are formed by means of explosive thermal deposition of InSb on semi-insulating GaAs(100) substrates in the temperature range of 375–460 °C. X-ray diffraction analysis established that the films are heteroepitaxial. It is shown that an increase in the deposition temperature of InSb films from 375 to 460 °C leads to a change in the film surface roughness (Ra) from 3.4 to 19.1 nm. The Hall voltage sensitivity to the magnetic field of InSb films varies in the range of 500–1500 mV/T. The electron concentration (n) and mobility (μ) changes in the range of 2 ⋅ 1016 – 6 ⋅ 1016 cm–3, 10 ⋅ 103 – 21 ⋅ 103 cm2/(V ⋅ s). The formed InSb films on semi-insulating GaAs(100) substrate are of practical interest for the manufacture of highly sensitive miniature Hall devices.
Keywords: indium antimonide; film; substrate; vacuum deposition; structure; electrical properties